Multiple Sources of Surprisal Affect Illusory Vowel Epenthesis - Whang, James (Frontiers in Psychology, 2021)
Illusory epenthesis is a phenomenon in which listeners report hearing a vowel between a phonotactically illegal consonant cluster, even in the complete absence of vocalic cues. The present study uses Japanese as a test case and investigates the respective roles of three mechanisms that have been claimed to drive the choice of epenthetic vowel---phonetic minimality, phonotactic predictability, and phonological alternations---and propose that they share the same rational goal of searching for the vowel that minimally alters the original speech signal. Additionally, crucial assumptions regarding phonological knowledge held by previous studies are tested in a series of corpus analyses using the Corpus of Spontaneous Japanese. Results show that all three mechanisms can only partially account for epenthesis patterns observed in human subjects, and the study concludes by discussing possible ways in which the mechanisms might be integrated.